La maîtrise du temps d’irrigation au sein des oasis alimentées par des aflâj - Julien Charbonnier (Revue d'ethnoécologie)
The irrigation technique prevailing in Oman oases, the falaj, delivers water year round. The users of a falaj have to divide its water on a temporal basis. Each of them is allocated a certain number of 30-minute water shares. Sundials were traditionally used to calculate these shares. This is still the case in the oasis of Adam. The inhabitants of this oasis do not take into account a spatial order to allocate water. Each of them can use his share for any one of the plots he owns. This method of distribution contrasts with the one used in Southwestern Arabia. In that region, the water goes through the entire irrigation system from upstream to downstream, plot after plot. The temporal management of water used in Oman presents some technical inconvenience. Between two plots, water must sometimes run long distance. However, this method allows the system to be more flexible and is favourable to the cultivation of annual plants. It is also suitable for the date palm, the key plant of the oasis.